Design of a general type BSSO fixation plate integrating topology and parameter optimization for various severity levels of hemifacial microsomia - Chang, Chun-Ming; Wang, Po-Fang; Wang, Yu-Tzu (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionPatients with hemifacial microsomia exhibit varying degrees of mandibular asymmetry. The commercial plates used during bilateral sagittal split osteotomy (BSSO) surgery are often not tailored to individual patients and may lack sufficient fixation stability, increasing the risk of mandibular relapse. This study proposes a patient-specific plate design by collecting CT images of 30 cases of hemifacial microsomia to statistically analyze mandibular asymmetry.MethodsThe design process integrates topology and parameter optimization analysis to develop the plate (TOPO plate), aiming for a lightweight structure with enhanced fixation stability. The structural strength and fixation stability of the TOPO plate were verified through static and dynamic four-point bending tests, as well as biomechanical testing, ensuring compliance with clinical requirements and regulatory approval for market release.ResultsThe TOPO plate features an asymmetrical design tailored to patient’s specific anatomy. In static/dynamic four-point bending tests, the structural strength of the TOPO plate exceeded that of commercial plates, with average proof loads of 326.9N for the right side and 389.85N for the left side. Biomechanical analysis and testing confirmed that the TOPO plate effectively limits the displacement of the mandibular segment (average 0.45mm), providing favorable fixation stability and thereby reducing the risk of relapse.DiscussionIn summary, the TOPO plate is applicable for most patients with hemifacial microsomia, meeting the biomechanical requirements of the mandible and complying with market conditions. This patient-specific approach promises improved outcomes in mandibular fixation stability.